Anti-biofouling superhydrophilic membrane - Christopher (Nanyang Technological University, 2020)
Biocorrosion and membrane biofouling has been a persisting problem in the water treatment industry caused by microorganism activity in the feed stream. The combination of these may cause structural failures (e.g., potable water distribution pipeline and cooling systems) and a rapid decline in the water flux recovery from the wastewater over time. To prolong the structural integrity and membrane life, one of the most common methods used is the chemical cleaning which involves the application of corrosive chemicals for treatment. Several efforts to shift away from the use of corrosive chemicals have been made, particularly in the use of metal oxides. Copper oxide (CuO) is one of the materials under the spotlight due to its low cost and comparable antimicrobial property to that of silver oxide and titanium (IV) oxide. Inspired by the sea turtle’s feeding method, the papillae structure displays an interconnected cross-linked network which promotes solids retention and allows water to pass through and enter their digestive system. Similarly, the FESEM & SEM analysis showed the successful deposition of copper precursors, followed by the self-aggregation into CuO on the membrane matrices to form the CuO Nano-structure PSf membrane, as verified through EDX analysis. The membrane morphology mimics the sea turtle’s papillae structure that can retain suspended solids and introduces higher surface area for more effective leaching of Cu2+ ions into the water to deter bacterial survivability and growth. Video contact angle (VCA) test also showed high hydrophilicity of the CuO Nano-structure PSf membrane with 17.4o wettability angle, which increased the continual repulsive interaction energy to enhance the anti-biofouling property. Antibacterial susceptibility testing by agar diffusion assay of the CuO Nano-structure PSf membrane was done against extensive species of bacteria, i.e., hand, mouth, MBR aerobic tank, E. coli K12, and S. aureus 15981. The results showed significant inhibitory activity through both physical (shown in the unsoaked membrane case where induction of ROS causes cell death) and chemical (shown in the soaked membrane case where a series of redox reaction of Cu2+ compromises cell integrity and protein production by the DNA, leading to cell death) pathway. ICP-OES test showed that there is a continual soaking duration up to 192 hours and showed a possible increment of leaching as time progresses. The overall results demonstrated that the CuO Nano-structure PSf membrane possesses good antibacterial activity against extensive strains commonly found in industrial wastewater. It also possesses the anti-biofouling property to inhibit the spread and growth of biofilms.